An Evaluation of a Modified CTAS at an Accident and Emergency Department in a Developing Country - Shalini Pooransingh; L. K. Teja Boppana; Isaac Dialsingh (Emergency Medicine International)
Objectives. To review the modified Canadian Triage and Acuity Scale used in an accident and emergency department in Trinidad and Tobago. Design and Methods. A cross-sectional study was carried out. Times from assignment of triage category to being seen by a physician were collected from the patient notes on the days of presentation and compared to the reference standards. Times from decision to admit to obtaining a bed were also recorded. Results. 200 patients were included in the study. The median waiting time for patients in the immediate/blue category was 3 minutes (range = 3); for the red category, it was 31.2 minutes (range = 121.8); in the yellow category, it was 61.8 minutes (range = 805.2). The overall admission rate was 30.5%, with an admission rate of 25% for the blue category; 20% of patients in the red category waited more than 4 hours for a hospital bed. Conclusion. The patients assigned to the blue category were being seen almost immediately. Less critical persons wait longer than the reference times and this may be due to structural factors such as staffing. The admission rates per category highlighted a low admission rate for the blue category (25%), which is unusual. This study highlights the need for a further study to review clinical presentation, assignment to triage category, and outcomes.